Analisis Pemenuhan Modal Minimum (Capital Adequacy Ratio ) dan Pendapatan Bagi Hasil Pembiayaan Mudharabah terhadap Tingkat Pengembalian Aset (Return on Asset): (Studi Kasus pada Bank Mandiri Syariah Tahun 2019) - Yusuf; Dian Endah Reswanti; Siti Pamrih Anjas Wulandari (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2021)
This research aim to to analyse influence of variable Capital Adequacy Ratio and earnings of defrayal sharing holder mudharabah to asset rate of return ( Return On Assets). In this research of data the used is data sekunder in the form of financial statement PT. Bank Mandiri Syariah from January up to December 2019. Technique analyse the data in descriptive research type kuantitaif this use the classic assumption test, significance test parsial and simultan, and also doubled linear regression test. Pursuant to examination result to Capital Adequacy Ratio and factor earnings of defrayal sharing holder mudharabah express that Variabel Capital Adequacy Ratio don't have the influence signifikanly to storey level Return on Asset, earnings of defrayal sharing holder mudharabah have the influence signifikan to storey level Return on Asset, variable earnings of sharing holder mudharabah and capital adequacy ratio concurrently ( simultan) can have an effect on signifikanly to storey level Return on Asset